The Mycobacterial Cell Envelope: A Relict From the Past or the Result of Recent Evolution? - Vincent, Antony T.; Nyongesa, Sammy; Morneau, Isabelle; Reed, Michael B.; Tocheva, Elitza I.; Veyrier, Frederic J. (Frontiers in Microbiology, 2018)
Mycobacteria are well known for their taxonomic diversity, their impact on global health, and for their atypical cell wall and envelope. In addition to a cytoplasmic membrane and a peptidoglycan layer, the cell envelope of members of the order Corynebacteriales, which include Mycobacterium tuberculosis, also have an arabinogalactan layer connecting the peptidoglycan to an outer membrane, the so-called “mycomembrane”. This unusual cell envelope composition of mycobacteria is of prime importance for several physiological processes such as protection from external stresses and for virulence. Although there have been recent breakthroughs in the elucidation of the composition and organization of this cell envelope, its evolutionary origin remains a mystery. In this perspectives article, the characteristics of the cell envelope of mycobacteria with respect to other actinobacteria will be dissected through a molecular evolution framework in order to provide a panoramic view of the evolutionary pathways that appear to be at the origin of this unique cell envelope. In combination with a robust molecular phylogeny, we have assembled a gene matrix based on the presence or absence of key determinants of cell envelope biogenesis in the Actinobacteria phylum. We present several evolutionary scenarios regarding the origin of the mycomembrane. In light of the data presented here, we also propose a novel alternative hypothesis whereby the stepwise acquisition of core enzymatic functions may have allowed the sequential remodeling of the external cell membrane during the evolution of Actinobacteria and has led to the unique mycomembrane of slow-growing mycobacteria as we know it today.